IDENTIFIKASI MASKULINITAS DALAM PERSPEKTIF GENDER DI FILM MANUSIA SETENGAH SALMON - Albertus Widya Dewanta; Paku Kusuma; Hyacinta Laras Permata Siwi (KalaTanda, 2020)
Gender is a characteristic that is used to differentiate between men and women, not only in physical form, but also in terms of culture, behavior, emotions, socio-culture, and others. When discussing gender theory, it cannot be separated from sociology and psychology. The practice of gender theory is not only used in everyday life, but also in filmmaking. The film uses gender theory as a reference according to the story that will be raised. However, in a film that uses gender theory, it doesn't have to have men and women in every problem that will be made in the film. The relationship between children and fathers can also be explored using gender theory. This journal will explain about the character of Dika's father in the film Human Half Salmon from the point of view of gender theory, especially masculinity because in the film there are several changes in the nature of masculinity towards the character of Dika's father. Keywords: Masculinity, Dika’s father characteristic, Film “Manusia Setengah Salmon”.